PENERAPAN LATIHAN TERBIMBING PADA KEGIATAN EKSTRAKURIKULER PADUAN SUARA DI SMK NEGERI 3 PADANG - Khaira Syadrini; Jagar Lumbantoruan; Tulus Handra Kadir (SENDRATASIK UNP, 2018)
Abstract This article aims to describe the implementation of guided training on unisono choir extracurricular activities at SMK Negeri 3 Padang. This research was a qualitative research with descriptive analysis approach. The unisono choir extracurricular activities program with guided training are as follows: the teacher's first meeting explained the material about the choir and some choir concepts. In the second meeting, the teachers taught basic choir techniques exercises. At the third meeting, the teachers taught reading Indonesia Raya numeric notation by applying the techniques which were already learned previously. In the fourth meeting, teachers taught reading the lyrics of Indonesia Raya song. Then the fifth meeting was a combined performance. From the result of the research, it is found that the extracurricular activities of the choir at SMK Negeri 3 Padang with the implementation of guided training included sound production was more stable; when voicing intonation, either rhythmically or melody is appropriate. Students sang the phrase or sentence of the song (lyrics) has been good. The lyrical messages of the song were delivered or sung in clear, and the expression is much better. The technique used has begun perfectly because, in every meeting, the students were always practising the material that has been taught in the last week so that the ability of the sound more harmonious. Assessment techniques are performed.  Indicator assessed or which need to be improved is in terms of sound, harmonization and technique in singing. Keywords: Guided Exercise, Choir